THE COMPETENCY-BASED APPROACH AS METHODOLOGY OF PROFESSIONAL TRAINING OF FUTURE TEACHERS IN THE CONDITIONS OF EDUCATION INFORMATIZATION - Kharkivska , A. (Problems of Engineer-Pedagogical Education, 2021)
Economic, sociocultural and informational changes taking place in modern society, actualize the need to modernize the training system for future teachers. One of the main tasks of higher education should be quality training of a teacher, highly qualified, competent, competitive in the labor market, who will freely own their profession and navigate in related fields, ready for continuous professional development, selfeducation. By signing the Bologna declaration, Ukraine has legitimized the competence base of the state educational paradigm. The study is devoted to the issue of competency-based approach as methodology of professional training of future teachers in the conditions of education informatization. Based on the data of scientific achievements, the article analyzes and defines the essence of the concepts «competency-based approach», «competency», «competence». The main key competencies (including informative) that graduates of higher pedagogical education institutions should acquire are considered. The author determined that the competency-based approach, in contrast to the traditional approach, involves not only acquiring knowledge, skills and abilities, but also forming and developing students’ ability to adapt and act independently in standard and non-standard situations, quickly solve problems of varying complexity on the basis of acquired knowledge; competency means the level of education, ie mastering the necessary competences, and competence is considered a set of personality qualities that ensures the success of professional activities; information competence is interpreted as an integral quality of personality, the ability to use modern information and digital technologies in professional activities and the ability to model and design information and educational activities. The main principles of the competency-based approach are: orientation of the educational process on the formation and development of key and subject competencies of the individual; reorientation from the process to the result of education in the activitypersonality-oriented dimension; students’ ability to solve problems that arise in different areas of activity.